Influence of soil texture, land cover, and photosynthetic activity on the flora composition of three altitudinal gradients of the Potrerillo wetland in the Chimborazo reserve - Muñoz-Jácome, Eduardo Antonio; Yanqui-Ushiña, Javier Felix; Abarca- Bonilla, Elizabeth Mariela; Vaca-Cárdenas, Maritza Lucia; Brito-Mancero, Marcela Yolanda; Cushquicullma-Colcha, Diego Francisco; Vaca-Cárdenas, Pedro Vicente (Edelweiss Applied Science and Technology, 2026)
The Potrerillo wetland (Chimborazo Reserve, Ecuador, 4318 m a.s.l.) is a fragile ecosystem due to its importance for water regulation and carbon storage, threatened by glacial retreat and anthropogenic activities. This study analyzed the influence of soil texture, land cover, and photosynthetic activity on floristic composition at three altitudinal gradients (low: 4280–4306.6 m; middle: 4306.7–4333.2 m; high: 4333.3–4360 m). Using DJI M200 drones and multispectral sensors, an NDVI between 0.6 and 0.8 was determined, reflecting high photosynthetic activity. Fourteen species and nine families were inventoried, with Asteraceae being dominant (Calamagrostis intermedia, Distichia muscoides). Diversity ranged from moderate to low, with greater richness at the top of the gradient and interspecific competition at the middle and top levels. Statistical results identified two key components: Factor 1, which links soil texture and cover with lower diversity; and Factor 2, which establishes a positive correlation between photosynthetic assimilation and floristic richness. Redundancy analysis (RDA) integrated floristic and edaphic variables, confirming ecological gradients defined by the interaction between photosynthetic capacity and soil physical properties. The study demonstrates that floristic composition, ecosystem productivity, and plant diversity depend on edaphic and hydrological conditions and vegetation cover.